Intermolecular Diels-Alder Cycloadditions of Furfural-Based Chemicals from Renewable Resources: A Focus on the Regio- and Diastereoselectivity in the Reaction with Alkenes - Konstantin I. Galkin (MDPI AG, 2021)
A recent strong trend toward green and sustainable chemistry has promoted the intensive use of renewable carbon sources for the production of polymers, biofuels, chemicals, monomers and other valuable products. The Diels-Alder reaction is of great importance in the chemistry of renewable resources and provides an atom-economic pathway for fine chemical synthesis and for the production of materials. The biobased furans furfural and 5-(hydroxymethyl)furfural, which can be easily obtained from the carbohydrate part of plant biomass, were recognized as “platform chemicals” that will help to replace the existing oil-based refining to biorefining. Diels-Alder cycloaddition of furanic dienes with various dienophiles represents the ideal example of a “green” process characterized by a 100% atom economy and a reasonable E-factor. In this review, we first summarize the literature data on the regio- and diastereoselectivity of intermolecular Diels-Alder reactions of furfural derivatives with alkenes with the aim of establishing the current progress in the efficient production of practically important low-molecular-weight products. The information provided here will be useful and relevant to scientists in many fields, including medical and pharmaceutical research, polymer development and materials science.